Single Proteoliposomes with E. coli Quinol Oxidase: Proton Pumping without Transmembrane Leaks. Issue 5 (10th February 2017) - Berg, Johan; Block, Stephan; Höök, Fredrik; Brzezinski, Peter
Abstract: Respiratory oxidases are transmembrane enzymes that catalyze the reduction of dioxygen to water in the final step of aerobic respiration. This process is linked to proton pumping across the membrane. Here, we developed a method to study the catalytic turnover of the quinol oxidase, cytochrome bo 3 from E. coli at single‐molecule level. Liposomes with reconstituted cytochrome bo 3 were loaded with a pH‐sensitive dye and changes in the dye fluorescence, associated with proton transfer and pumping, were monitored as a function of time. The single‐molecule approach allowed us to determine the orientation of cytochrome bo 3 in the membrane; in ∼70 % of the protein‐containing liposomes protons were released to the outside. Upon addition of substrate we observed the buildup of a ΔpH (in the presence of the K + ionophore valinomycin), which was stable over at least ∼800 s. No rapid changes in ΔpH (proton leaks) were observed during steady state proton pumping, which indicates that the free energy stored in the electrochemical gradient in E. coli is not dissipated or regulated through stochastic transmembrane proton leaks, as suggested from an earlier study (Li et al. J. Am. Chem. Soc . (2015) 137, 16055–16063). Abstract :